Comparison Of Three Different Treatment Methods For Cesarean Scar Pregnancy - Fei H (Dove Medical Press, 2019)
Hui Fei,1,* Xuefeng Jiang,2,* Tian Li,1 Ying Pan,2 Hongling Guo,1 Xiaoyu Xu,1 Shanrong Shu2 1Department of Gynecology and Obstetrics, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen 518107, People’s Republic of China; 2Department of Gynecology and Obstetrics, The First Afﬁliated Hospital of JiNan University, Guangzhou 510630, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shanrong ShuDepartment of Gynecology and Obstetrics, The First Afﬁliated Hospital of JiNan University, 613 Huangpu Road West, Guangzhou 510630, People’s Republic of ChinaTel +86-20-38688769Fax +86-20-38688769Email butterfly1705@126.comBackground/Aim: Cesarean scar pregnancy is a long term complication of cesarean section. There is a lot of controversy about the best treatment methods. We retrospectively summarized the clinical characteristics of patients with cesarean scar pregnancy and explored the advantages and disadvantages of fertility-preservation treatment method.Methods: From January 2008 to September 2017, a total of 204 cases of cesarean scar pregnancy were retrospectively reviewed. 145 patients underwent transvaginal clearance, 33 patients underwent endoscopic surgery, and 26 patients underwent uterine artery embolism. The clinical characteristics, diagnosis, various treatment methods, and clinical outcomes were analyzed.Results: There were no significant differences among the three groups in terms of patient age, number of previous cesarean sections, serum human chorionic gonadotropin, and clinical symptoms. The difference in mean gestational sac diameter (23.5±2.1mm vs 31.3±2.4mm vs 30.8± 1.9mm), surgical time (31.4±2.5min vs. 45.8±2.2min vs. 51.4±1.9min), blood loss (53.3± 5.5mL vs. 105.2±3.2mL vs. 75.6 ±3.5mL), blood transfusion (1/145 case vs.3/33 case vs. 0/26 case), discomfort (1/145 case vs.9/33 case vs. 16/26 case), hospital stay (6.1±1.1 day vs. 7.4±0.9 day vs.18.6±1.5 day), fever duration (1.0±0.5 day vs. 2.1±2.8 day vs. 5.7±3.5 day), and hospital expense (¥ 7825.9±234.9 vs. ¥ 10248.3± 312.9 vs. ¥ 18774.9±243.6) in transvaginal pregnancy tissue clearance, endoscopic surgery, and uterine artery embolism groups were significantly different.Conclusion: Transvaginal clearance is an effective and relatively safe treatment option for patients with cesarean scar pregnancy.Keywords: cesarean scar pregnancy, transvaginal clearance, endoscopy, uterine artery embolism